A 410 MHz resonant cavity pickup for heavy ion storage rings - Sanjari, Mohammad Shahab; Dmytriiev, Dmytro; Litvinov, Yuri A.; Gumenyuk, O.; Hess, R.; Joseph, R.; Litvinov, S. A.; Steck, M.; Stöhlker, Thomas (Review of scientific instruments, 2020)
An improved design of a longitudinally sensitive resonant Schottky cavity pickup for the heavy ion storage rings of the Facility for Antiproton and Ion Research in Europe (FAIR) project is reported. The new detector has a higher measured Q value of ∼3000 and a higher simulated shunt impedance of 473.3 kΩ. It is possible to vary the sensitivity of the cavity with a motorized mechanism by inserting a dissipative blade during the operation based on experimental needs. Apart from a lower price tag, the new design features a more robust and production-friendly mechanical structure suitable for a series production in the future FAIR project. The manufactured cavity was built temporarily into the experimental storage ring and had delivered its first results using stored heavy ion beams. The structure, simulation results, and performance of this cavity are presented in this work.
Gesehen am 25.09.2020